Pengembangan Aparatur Sipil Negara (ASN) Di Dinas Komunikasi, Informatika Dan Persandian Kabupaten Mamuju - Risal, M; Razak, Andi Rosdianti; Haerana, Haerana (Universitas Muhammadiyah Makassar, 2020)
The purpose of the study is conducted to determine the development of the state civil apparatus also known as ASN in the communication, informatics and coding department of Mamuju Regency. The research method used is qualitative research with primary and secondary data collection techniques. The number of informants in this study are 6 people. The data collection techniques by means of documentation, observation, and interviews. The results of this study indicate that the education program for apparatus is still lacking motivation to the apparatus to continue their formal education to a higher level. In addition, the budget for ASN development programs in the Office of Informatics and the Mamuju Archipelago is very minimal, from the aspect of training programs to the apparatus in the Office of Informatics and the Mamuju Archipelago also conducts training for its apparatus, but it is still not consistent in its efforts seen in 2018 and 2019, the Mamuju Communication Information and Informatics Office do not send its apparatus in the Latpim activities organized by BKD and LAN.